Penerapan Model Project Based Learning pada Materi Sumber Daya Alam yang Terintegrasi Nilai-Nilai Keislaman untuk Meningkatkan Hasil Belajar Siswa Kelas V SDN 96 Campurejo Kab. Luwu - Nanda Mutiara Fadilla; Baderiah; Lilis Suryani (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to examine the implementation of the Project-Based Learning (PjBL) model, integrated with Islamic values, in the natural resources curriculum, as well as to improve the learning outcomes of Year 5 pupils at SDN 96 Campurejo, Luwu Regency. This study employed a Classroom Action Research (CAR) design conducted over two cycles, each comprising the stages of planning, implementation, observation, and reflection. The research subjects consisted of 22 Year 5 pupils. Data collection techniques included observation, learning outcome tests, and documentation. The data analysis techniques used included qualitative analysis to examine teacher and student activities during learning, as well as quantitative analysis to analyse student learning outcomes through the calculation of average scores and the percentage of learning achievement. The results of the study indicate that the application of the PBL model integrated with Islamic values is capable of improving student learning outcomes. This is demonstrated by an increase in the students’ average score from 69.09 with a learning achievement rate of 59.05% in Cycle I to 81.81 with a learning achievement rate of 81.81% in Cycle II, thereby achieving the class standard. Thus, the implementation of the Project-Based Learning model based on Islamic values is effective in improving students’ learning outcomes in the subject of natural resources at primary school level